Isolat Bakteri Asam Laktat Sebagai Probiotik dengan Vaksinasi AI dan ND dalam Pembentukan Titer Antibodi Dan Bobot Badan Ayam Jantan Tipe Medium - Rudy Sutrisna (Jurnal Penelitian Pertanian Terapan, 2014)
Isolates of Lactic Acid Bacteria isolates assembled into a mixture of LAB as probiotics . LAB probiotic drops introduced through the mouth with the aim of suppressing pathogens and is expected to improve the health status of rooster type of medium . Isolates in the digestive tract will undergo adaptation by temperature , acidity and pH changes in the gut . The health status of the chicken can be expressed as growth to form the body weight , and the growth of LAB . In addition , AI and ND vaccination in healthy chickens conditions will produce antibodies to both . The success of vaccination can be evaluated from the results of the formation of chicken blood serum titre of research . Analysis of descriptive data on the dynamics of the growth of LAB , the formation of antibody titer and body weight gain 24-31 day old chickens . Based on the results of this study revealed that isolates of LAB can be used simultaneously in bercoccidiostat feed . LAB isolates may develop in the digestive tract rooster medium type as probiotics. The dynamics of the growth of a population produces a mixture of isolates of LAB isolates (mixture of B1, B3, B4, B5 as probiotics) in the highest reaches of the ilium and jejunum 14.00 x 10-6 13.5 x 10-6 CFU/ml. Test isolates viability of probiotic candidates in all isolates produced distilled water medium can live up to 72 hours of incubation . In addition, there is a synergy results in the formation of antibody titers ND uniform T3 treatment. T3 treatment is given probiotics 2x chicken every week for 3 weeks . In AI vaccination resulted in antibody titers are not uniform. Body weight gain reached the age of 24-31 days in a row 75.83 g, 76.54 g, 81.58 g, 87.04 g. Weight age of 31 days the average value obtained successively from the highest 329.16 g, 328.54 g, 325.54 g and 324.08 g lowest . Keywords; isolates LAB, probiotics, antibody titers, rooster layer medium type.